2019
DOI: 10.7150/ijms.38502
|View full text |Cite
|
Sign up to set email alerts
|

Lipid emulsion inhibits the vasodilation induced by a toxic dose of amlodipine in isolated rat aortae

Abstract: The goal of this study was to examine the effect of lipid emulsion on the vasodilation induced in isolated endothelium-denuded rat aortae by a toxic dose of amlodipine. We examined the effects of lipid emulsion and verapamil on amlodipine-induced vasodilation. We also examined the effects of a mixture of lipid emulsion and amlodipine, as well as the centrifuged aqueous extract (CAE) obtained by ultracentrifuging such a mixture and then removing the upper lipid layer, on amlodipine-induced vasodilation. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 34 publications
4
10
0
Order By: Relevance
“…Studies have shown that lipid emulsion reduces the concentration of drugs with a high lipid solubility (log [octanol/water] partition coefficient: >2), such as bupivacaine, verapamil, and amlodipine, by sequestrating drug molecules on the lipid phase of the emulsion. 7,8,24 Consistent with these findings of previous studies, lipid emulsion-mediated slight reduction in amlodipine concentration in this study might have partially contributed to the inhibition of amlodipine-induced decrease in cell viability. 7,8,24…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Studies have shown that lipid emulsion reduces the concentration of drugs with a high lipid solubility (log [octanol/water] partition coefficient: >2), such as bupivacaine, verapamil, and amlodipine, by sequestrating drug molecules on the lipid phase of the emulsion. 7,8,24 Consistent with these findings of previous studies, lipid emulsion-mediated slight reduction in amlodipine concentration in this study might have partially contributed to the inhibition of amlodipine-induced decrease in cell viability. 7,8,24…”
Section: Discussionsupporting
confidence: 92%
“…7,8,24 Consistent with these findings of previous studies, lipid emulsion-mediated slight reduction in amlodipine concentration in this study might have partially contributed to the inhibition of amlodipine-induced decrease in cell viability. 7,8,24…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Minoxidil (10 -4 M) in Krebs solution was mixed with Intralipid (0.5, 2 and 5%) using a rotator for 30 min to emulsify the minoxidil and lipid emulsion, as previously described (Ok et al 2019a). After centrifugation at 75,000 × g for 40 min, the minoxidil concentration in the aqueous phase was measured by ultraperformance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF MS; Waters, Milford, MA, USA) with multiple reaction monitoring (MRM).…”
Section: Effect Of Lipid Emulsion On Minoxidil Concentration In Krebs Solutionmentioning
confidence: 99%